Test method of pole piece flexibility and application
Patent Information
- Application Number
- CN202611256992.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-27
AI Technical Summary
该方法依靠人工目视判定折痕处的透光程度,主观性强且难以量化,无法区分轻微损伤与临界失效状态
本发明提供的测试方法,通过同步获取同一极片在n次弯折前后的吸液量变化、欧姆内阻变化和断裂拉力变化三组物理量,并据此计算柔韧性数值S,实现了对极片柔韧性的多维度、定量、可复现评价。其中,吸液量变化敏感反映弯折导致的粉料-集流体界面剥离及微裂纹扩展所引起的毛细通道劣化;欧姆内阻RS变化直接表征电子传导通路完整性;断裂拉力变化则客观量化机械延展与结构承载能力衰减。三者协同克服了单一指标无法全面覆盖机械性能退化、粘结力损失、电学通路劣化三大柔韧性本质维度的技术缺陷。且所有参数均基于同一极片在相同弯折次数下的实测数据,消除了样品批次差异干扰,显著提升测试精度与工艺指导价值。
Smart Images

Figure CN122982811A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrode quality management technology, and in particular to a method and application for testing electrode flexibility. Background Technology
[0002] With the increasing demand for driving range in the new energy vehicle and energy storage sectors, lithium-ion battery energy density has become a core R&D indicator. Under a given material system, increasing the compaction density of the positive and negative electrode sheets is an effective way to improve volumetric energy density. However, while increasing the active material loading, high compaction processes significantly reduce the internal porosity of the electrode sheets, leading to increased coating brittleness and a decrease in the fatigue limit of the current collector, thus posing a severe challenge to the flexibility of the electrode sheets. Insufficient electrode flexibility can easily cause breakage, powder shedding, and microcracks during cell winding / stacking, subsequently inducing safety hazards such as cycle failure and internal short circuits. Therefore, how to accurately and quantitatively assess electrode flexibility has become a common industry problem restricting the development of high-energy-density batteries.
[0003] Currently, the industry's assessment methods for electrode flexibility mainly cover several dimensions, including light transmission observation, mechanical performance testing, internal resistance detection, and powder shedding analysis. Among these, the light transmission observation method, which involves observing whether light passes through the crease after folding, has become the most common qualitative screening method on the production line due to its ease of operation. However, this method relies on manual visual judgment of the light transmission level at the crease, which is highly subjective, difficult to quantify, and cannot distinguish between minor damage and critical failure.
[0004] Furthermore, existing mechanical performance tests (such as tensile strength) can only reflect the overall mechanical strength of the electrode and cannot specifically characterize local damage at the crease; internal resistance tests usually focus on the overall conductivity of the electrode and are difficult to separate the interface contact degradation component caused by bending; while the assessment of powder shedding is mostly done by tape adhesion or ultrasonic vibration methods, which can reflect the bonding force but cannot simulate the dynamic failure process of the electrode under bending stress.
[0005] The above methods are mostly single-dimensional offline detection methods, and generally suffer from defects such as low quantification, high susceptibility to human factors, and inability to establish a direct mapping relationship with electrochemical performance, making it difficult to meet the needs of refined development and quality control of high-voltage real electrode sheets.
[0006] In view of this, the present invention is hereby proposed. Summary of the Invention
[0007] The purpose of this invention is to provide a method and application for testing electrode flexibility, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0008] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: The first aspect of the present invention provides a method for testing the flexibility of an electrode sheet, comprising the following steps: A. Obtaining the initial liquid absorption volume ΔW of the electrode sheet to be tested. 基准 Initial electrode internal resistance R S基准 and initial fracture tensile force M 基准 B. After bending the electrode to be tested n times and restoring it to its original shape, test the liquid absorption ΔW of the electrode after n bends. n , electrode internal resistance R Sn and tensile strength at break M n Where n is a positive integer and the electrode under test does not break after the nth bend; C, calculate the electrode flexibility value S after n bends by the changes in liquid absorption, electrode internal resistance and breaking tensile force after n bends; D, the test ends when the electrode breaks.
[0009] In some embodiments of the present invention, the method for testing the liquid absorption is as follows: the electrode to be tested is placed in the electrolyte, so that any position between the crease and the tail end is flush with the liquid surface, after soaking, it is taken out, the surface droplets are drained, the weight is weighed and the mass increment is calculated to obtain the liquid absorption.
[0010] Preferably, the soaking time is 3 to 6 hours.
[0011] Preferably, the midpoint line between the crease and the bottom surface of the electrode is aligned with the liquid surface.
[0012] In some embodiments of the present invention, the method for testing the ohmic internal resistance of the electrode is as follows: two electrodes to be tested are made into a symmetrical cell, and electrochemical impedance spectroscopy (EIS) is used for testing. The scanning frequency is 10 mHz~100 kHz and the amplitude is 10 mV. The Rs value corresponding to the real axis intercept in the high-frequency region is extracted as the ohmic internal resistance of the electrode.
[0013] Preferably, the electrolyte in the symmetrical battery is the same as the electrolyte in the liquid absorption test.
[0014] In some embodiments of the present invention, the method for testing the breaking tensile force is as follows: the two ends of the electrode to be tested are fixed in the fixture of a tensile testing machine, stretched at a constant rate, and the maximum tensile force value corresponding to the moment the electrode breaks is recorded as the breaking tensile force.
[0015] Preferably, the stretching rate is 20~100 mm / min.
[0016] In some embodiments of the present invention, the electrode flexibility value S after n bends is positively correlated with the weighted sum of the liquid absorption retention rate of the bent electrode relative to the unbent state, the reciprocal of the degradation of ohmic internal resistance, and the tensile strength retention rate at break.
[0017] In some embodiments of the present invention, the liquid absorption retention rate is ΔW n / △W 基准The inverse of the degradation of the ohmic internal resistance is R. S基准 / R Sn The tensile strength retention rate at break is M. n / M 基准 ; The electrode flexibility value S = α·△W n / △W 基准 +β·R S基准 / R Sn +γ·M n / M 基准 ; Among them, α, β, and γ are weight coefficients respectively, and 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1.
[0018] In some embodiments of the present invention, α is a weighting coefficient for cycle performance; β is a weighting coefficient for fast charging performance; and γ is a weighting coefficient for winding process adaptability.
[0019] The values of α, β, and γ are determined by the priority of the corresponding performance requirements in actual engineering.
[0020] In some embodiments of the present invention, when the focus is on the cycle performance of the battery in actual engineering, α≥0.4; or, when the focus is on the fast charging performance of the battery in actual engineering, β≥0.4; or, when the focus is on the adaptability of the battery winding process in actual engineering, γ≥0.4.
[0021] In some embodiments of the present invention, the bending is performed along the centerline of the long side of the electrode to be tested.
[0022] Preferably, the bending angle is 0° to 180° and does not include 0°, and is preferably 90° or 180°.
[0023] The second aspect of this invention provides the application of the aforementioned testing method in electrode screening, roll forming process optimization, coating / die-cutting parameter verification, or electrode quality consistency control.
[0024] Compared with the prior art, the present invention has at least the following beneficial effects: The testing method provided by this invention simultaneously acquires three sets of physical quantities—the change in liquid absorption, the change in ohmic resistance, and the change in tensile strength at break—before and after n bends of the same electrode, and calculates the flexibility value S based on these quantities. This achieves a multi-dimensional, quantitative, and reproducible evaluation of the electrode's flexibility. Specifically, the change in liquid absorption sensitively reflects the deterioration of capillary channels caused by the peeling of the powder-current collector interface and the propagation of microcracks due to bending; the ohmic resistance R... SChanges directly characterize the integrity of the electron conduction pathway; changes in tensile strength objectively quantify the decrease in mechanical elongation and structural load-bearing capacity. The synergy of these three factors overcomes the technical limitations of a single indicator in comprehensively covering the three essential dimensions of flexibility: mechanical performance degradation, adhesive force loss, and electrical pathway deterioration. Furthermore, all parameters are based on measured data from the same electrode under the same number of bending cycles, eliminating interference from batch-to-batch sample differences and significantly improving testing accuracy and process guidance value.
[0025] Given the advantages of the above testing methods, standardized and instrumented evaluation criteria are provided for electrode screening, roll forming process optimization, coating / die-cutting parameter verification, or electrode quality consistency control. This significantly reduces the process debugging cycle and lowers the trial and error costs and production line omission risks caused by hidden damage. Attached Figure Description
[0026] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0027] Figure 1 This is a schematic diagram of an electrode sheet folded in half; Figure 2 This is a schematic diagram of the electrode absorbing liquid. Figure 3 A schematic diagram of a symmetrical battery assembly; Figure 4 This is the equivalent circuit diagram of EIS. Detailed Implementation
[0028] To make the objectives, technical solutions, and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0029] In the following, the terms “comprising,” “having,” and their cognates, which may be used in various embodiments of the invention, are intended only to indicate a particular feature, number, step, operation, element, component, or combination thereof, and should not be construed as excluding, firstly, the presence of one or more other features, numbers, steps, operations, elements, components, or combinations thereof, or adding the possibility of one or more features, numbers, steps, operations, elements, components, or combinations thereof.
[0030] The first aspect of the present invention provides a method for testing the flexibility of an electrode sheet, comprising the following steps: A. Obtaining the initial liquid absorption volume ΔW of the electrode sheet to be tested. 基准Initial electrode internal resistance R S基准 and initial fracture tensile force M 基准 B. After bending the electrode to be tested n times and restoring it to its original shape, test the liquid absorption ΔW of the electrode after n bends. n , electrode internal resistance R Sn and tensile strength at break M n Where n is a positive integer and the electrode under test does not break after the nth bend; C, calculate the electrode flexibility value S after n bends by the changes in liquid absorption, electrode internal resistance and breaking tensile force after n bends; D, the test ends when the electrode breaks.
[0031] The testing method provided by this invention simultaneously acquires three sets of physical quantities—the change in liquid absorption, the change in ohmic resistance, and the change in tensile strength at break—before and after n bends of the same electrode, and calculates the flexibility value S based on these quantities. This achieves a multi-dimensional, quantitative, and reproducible evaluation of the electrode's flexibility. Specifically, the change in liquid absorption sensitively reflects the deterioration of capillary channels caused by the peeling of the powder-current collector interface and the propagation of microcracks due to bending; the ohmic resistance R... S Changes directly characterize the integrity of the electron conduction pathway; changes in tensile strength objectively quantify the decrease in mechanical elongation and structural load-bearing capacity. The synergy of these three factors overcomes the technical limitations of a single indicator in comprehensively covering the three essential dimensions of flexibility: mechanical performance degradation, adhesive force loss, and electrical pathway deterioration. Furthermore, all parameters are based on measured data from the same electrode under the same number of bending cycles, eliminating interference from batch-to-batch sample differences and significantly improving testing accuracy and process guidance value.
[0032] Initial liquid absorption volume △W 基准 It refers to the mass increment of the electrode under test after standard immersion and draining without any bending. It reflects the comprehensive structural characteristics of the electrode, such as initial porosity, coating-current collector interface bonding state and wettability. It serves as the normalized benchmark for subsequent calculation of liquid absorption retention rate.
[0033] Liquid absorption ΔW of the electrode after n bends n This refers to the mass increment of the same electrode under test after being bent in a specified manner n times and then returning to its original shape, measured according to the same standard; that is, the absolute liquid absorption capacity after bending. This value directly reflects the degree of damage to the electrode's microstructure caused by bending fatigue: such as the propagation of microcracks in the coating, peeling of the active material from the current collector interface, and pore collapse, leading to capillary channel deterioration and thus reducing electrolyte penetration and retention capacity; its value is relative to ΔW. 基准 Attenuation △W n / △W 基准 It is the key parameter that characterizes the degradation of flexibility.
[0034] In some embodiments of the present invention, such as Figure 1As shown, the bending is performed along the centerline of the long side of the electrode to be tested. This bending method refers to folding or repeatedly folding the electrode along its geometric centerline in the length direction to ensure that the stress concentration area is always located in the longitudinal center area where the coating and current collector are most typically bonded and where the process sensitivity is highest. This improves the representativeness and comparability of the test results, avoids edge effect interference, and simulates the core stress path in the inner layer of the core where the electrode is most prone to deformation in the actual winding process, making the test closer to the failure mechanism under real working conditions.
[0035] Preferably, the bending angle is 0° to 180° and does not include 0°, and is preferably 90° or 180°. The bending angle is defined as the interior angle between the two parts of the electrode after it is folded. The range of 0° to 180° (excluding 0°) means that actual deformation must occur: 0° corresponds to no folding, while 180° represents that the folded part completely overlaps with the stationary side.
[0036] During the folding test, the same electrode should be repeatedly and uniformly bent at a preset fixed bending angle (such as 90° or 180°) until macroscopic fracture occurs. While maintaining a consistent bending method, using a smaller bending angle allows for more precise gradual stress accumulation per unit deformation, thereby delaying abrupt failure and improving the ability to distinguish the flexibility degradation process and the statistical robustness of the test data.
[0037] In some embodiments of the present invention, such as Figure 2 As shown, the test method for liquid absorption is as follows: place the electrode to be tested in the electrolyte, so that any position between the crease and the tail end is flush with the liquid surface. After soaking, take it out, drain the surface droplets, weigh it and calculate the mass increment to obtain the liquid absorption.
[0038] Preferably, the immersion time is 3-6 hours, which ensures that the electrolyte fully penetrates the capillary channels of the electrode active coating and achieves stable liquid absorption measurement, while also taking into account testing efficiency and process operability. This duration reflects the wettability decay trend caused by bending-induced microstructural damage (such as interface peeling and crack propagation), and significantly shortens the single test cycle, adapting to the rapid quality control requirements of the production line.
[0039] Preferably, the midpoint line between the crease and the bottom surface of the electrode is aligned with the liquid surface. That is, the horizontal baseline corresponding to the point where the plane of the crease is located is half the vertical distance from the free bottom edge of the electrode is aligned with the liquid surface. This is to ensure that the contact position between the electrolyte and the electrode is consistent in each liquid absorption test, thereby eliminating the fluctuation of capillary rise caused by the difference in wetting height, improving the repeatability and comparability of liquid absorption measurement, and accurately reflecting the influence of local structural damage in the crease area on wetting behavior.
[0040] In some embodiments of the present invention, the method for testing the ohmic resistance of the electrode is as follows: Figure 3The two electrodes to be tested are used to construct a symmetrical cell, as shown. Figure 4 The results were obtained by electrochemical impedance spectroscopy (EIS) with a scanning frequency of 10 mHz to 100 kHz and an amplitude of 10 mV. The Rs value corresponding to the real intercept in the high-frequency region was extracted as the ohmic internal resistance of the electrode.
[0041] Preferably, the electrolyte in the symmetrical battery is the same as the electrolyte in the liquid absorption test. Using the same electrolyte as the liquid absorption test to prepare the symmetrical battery ensures that the electrochemical responses reflected by the change in ohmic internal resistance (Rs), such as interfacial contact degradation and conductive network damage, have a unified physicochemical basis with the pore structure / wetting degradation characterized by the liquid absorption. This avoids uncontrolled variables introduced by differences in electrolyte composition from interfering with the accuracy and attribution reliability of the flexibility evaluation.
[0042] In some embodiments of the present invention, the method for testing the breaking tensile force is as follows: the two ends of the electrode to be tested are fixed in the fixture of a tensile testing machine, stretched at a constant rate, and the maximum tensile force value corresponding to the moment the electrode breaks is recorded as the breaking tensile force.
[0043] Preferably, the stretching rate is 20~100 mm / min.
[0044] In some embodiments of the present invention, the electrode flexibility value S after n bends is positively correlated with the weighted sum of the liquid absorption retention rate of the bent electrode relative to the unbent state, the reciprocal of the degradation of ohmic internal resistance, and the tensile strength retention rate at break.
[0045] This invention provides a synergistic quantitative characterization of the three core functional degradation behaviors of electrodes under bending fatigue: liquid retention rate reflects microstructural integrity (pore connectivity, interfacial bonding force); the reciprocal of ohmic resistance degradation characterizes the stability of electron conduction pathways (degree of contact resistance deterioration); and fracture tensile strength retention rate quantifies the level of maintenance of macroscopic mechanical load-bearing capacity. By integrating these three values through a weighted sum, the flexibility value becomes a comprehensive index that is interpretable, configurable, and engineering-mappable: the higher the value, the stronger the electrode's ability to maintain its original performance across multiple failure dimensions.
[0046] In some embodiments of the present invention, the liquid absorption retention rate is ΔW n / △W 基准 The inverse of the degradation of the ohmic internal resistance is R. S基准 / R Sn The tensile strength retention rate at break is M. n / M 基准 ; The electrode flexibility value S = α·△W n / △W 基准 +β·R S基准 / R Sn+γ·M n / M 基准 ; Wherein, α, β, and γ are weighting coefficients, and 0 < α < 1, 0 < β < 1, 0 < γ < 1, α + β + γ = 1. The dynamic configuration of the weighting coefficients endows the flexibility values with the ability to be evaluated in a targeted manner for different application scenarios (such as cycle life, fast charging, and winding adaptation), truly realizing the leap of flexibility from empirical perception to measurable physical properties, and from discrete criteria to system decision-making.
[0047] In some embodiments of the present invention, α is a weighting coefficient for cycle performance; β is a weighting coefficient for fast charging performance; and γ is a weighting coefficient for winding process adaptability.
[0048] The values of α, β, and γ are determined by the priority of the corresponding performance requirements in actual engineering.
[0049] In some embodiments of the present invention, when the focus is on the cycle performance of the battery in actual engineering, α≥0.4; or, when the focus is on the fast charging performance of the battery in actual engineering, β≥0.4; or, when the focus is on the adaptability of the battery winding process in actual engineering, γ≥0.4.
[0050] The weighting coefficients are not fixed constants, but rather dynamically configured process priority mapping parameters based on actual R&D or production goals. When cycle life is the primary objective (e.g., energy storage batteries, long-life vehicle batteries), setting α≥0.4 highlights the core importance of electrolyte retention rate, as electrolyte wetting stability directly determines the uniformity of the SEI at the electrode / electrolyte interface and the long-term structural integrity. Microcrack-induced wetting failure is a key cause of cycle failure. When focusing on fast-charging performance (e.g., fast-charging platforms for power batteries), increasing β≥0.4 emphasizes the weight of the reciprocal of ohmic internal resistance degradation, as Joule heating and electron transport impedance are highly sensitive under fast charging. Rs degradation accelerates local overheating and polarization, becoming an early warning indicator of fast-charging rate bottlenecks. When optimizing the adaptability of winding processes (e.g., mass production of high areal density electrodes), increasing γ≥0.4 highlights the criterion role of tensile strength retention rate, as winding tension and radius of curvature directly test the electrode's elongation limit, and its mechanical load-bearing attenuation trend can accurately predict process anomalies such as production line breakage and powder shedding.
[0051] This design elevates the flexibility value S from a general indicator to a scenario-driven decision-making tool, supporting R&D in customizing evaluation standards as needed, and achieving closed-loop alignment between material design, process debugging, and end-application requirements.
[0052] The second aspect of this invention provides the application of the aforementioned testing method in electrode screening, roll forming process optimization, coating / die-cutting parameter verification, or electrode quality consistency control.
[0053] Given the advantages of the above testing methods, standardized and instrumented evaluation criteria are provided for electrode screening, roll forming process optimization, coating / die-cutting parameter verification, or electrode quality consistency control. This significantly reduces the process debugging cycle and lowers the trial and error costs and production line omission risks caused by hidden damage.
[0054] The present invention is further illustrated below with specific embodiments and comparative examples. However, it should be understood that these embodiments are merely for illustrative purposes and should not be construed as limiting the invention in any way. Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention were carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0055] Preparation Example 1: A positive electrode sheet with a double-sided areal density of 400 g / m² was fabricated. 2 The foil material is 13μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.7%:1.0%:0.5%:1.8%, with a roll compaction of 2.45g / cm. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0056] Preparation Example 2: A positive electrode sheet with a double-sided areal density of 400 g / m² was fabricated. 2 The foil material is 13μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.7%:1.0%:0.5%:1.8%, with a roll compaction of 2.65g / cm. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0057] Preparation Example 3: A positive electrode sheet with a double-sided areal density of 400 g / m² was fabricated. 2 The foil material is 13μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.0%:1.0%:0.5%:2.5%, with a roll compaction of 2.45g / cm. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0058] Preparation Example 4: Fabrication of a positive electrode sheet with a double-sided areal density of 400 g / m³ 2 The foil material is 15μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.7%:1.0%:0.5%:1.8%, with a roll compaction of 2.45g / cm³. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0059] Preparation Example 5: A positive electrode sheet with a double-sided areal density of 460 g / m² was fabricated. 2The foil material is 13μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.7%:1.0%:0.5%:1.8%, with a roll compaction of 2.45g / cm. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0060] Preparation Example 6: A positive electrode sheet with a double-sided areal density of 460 g / m² was fabricated. 2 The foil material is 13μm aluminum foil, and the loading paste is LFP:SP:CNT:PVDF = 96.7%:1.0%:0.5%:1.8%, with a roll compaction of 2.65g / cm. 3 After die-cutting, small pieces with a length of 85mm and a width of 65mm are obtained.
[0061] Example The electrode sheets prepared in Examples 1-6 were subjected to electrode flexibility testing. The specific steps are as follows: 1. Take a small, unbent piece of material and weigh it to obtain its initial mass W0. Then, immerse it in an electrolyte solution with a concentration of EC:DEC:EMC:LiPF6:PS:VC:LiFSI = 30%:25%:30%:12%:0.5%:0.5%:2%, ensuring the crease baseline (i.e., the center fold line) is flush with the liquid surface. After standing for 4 hours to absorb the liquid, remove the piece and gently wipe the surface free liquid with filter paper. Weigh the piece after liquid absorption to obtain W0′. Calculate the amount of liquid absorbed, ΔW. 基准 =W0′ W0.
[0062] 2. Take two more unbent small pieces from the same batch and assemble them into a symmetrical battery (separator: 722 wet-coated separator, electrolyte formula is the same as in step 1) and perform EIS testing (10 mHz~100 kHz, 10 mV amplitude). Extract the Rs value as R S基准 .
[0063] 3. Take another unbent piece and test it with a universal tensile testing machine (clamping distance 50 mm, tensile rate 30 mm / min). Record the maximum tensile force M at break. 基准 .
[0064] 4. Take another unbent piece from the same batch, manually fold it 180° along the center line and flatten it (record as one bend), and repeat the liquid absorption, EIS, and tensile tests in steps 1-3 above to obtain ΔW1 and R. S1 M1.
[0065] 5. Take another unbent piece from the same batch, manually fold it 180° along the center line and flatten it, then fold it 180° along the center line and flatten it again (recorded as 2 bends). Repeat the liquid absorption, EIS, and tensile tests in steps 1-3 above to obtain ΔW2 and R. S2 M2.
[0066] 6. Repeat step 5 to obtain the values for 3 bends, 4 bends, or 5 bends respectively.
[0067] 7. Substitute into the formula S=α·△W n / △W 基准 +β·R S基准 / R Sn +γ·M n / M 基准 With α=0.3, β=0.4, and γ=0.3, the obtained data are recorded in Table 1.
[0068] Table 1
[0069] As shown in Table 1, the flexibility value S decreases monotonically with increasing number of folds, and the rate of decrease varies significantly due to differences in process parameters. If the electrode breaks after a certain number of folds, the S value score is 0. During testing, the S values of different samples can be compared laterally at the same number of folds, or the flexibility differences of a single sample can be compared longitudinally at different numbers of folds. Using Preparation Example 1 as the baseline comparison group, the influence of different parameter changes on the electrode flexibility is examined. Preparation Example 2, compared to Preparation Example 1, has a higher compaction density (industry standards indicate that higher compaction results in poorer flexibility). The data table shows that its liquid absorption capacity is worse than that of Preparation Example 1, the change in Rs value is not as significant as that of Preparation Example 1, its tensile strength is worse than that of Preparation Example 1, and the S value is smaller after the same number of folds compared to Preparation Example 1. This provides a quantitative indication of the flexibility difference between the two, and also shows the trend of flexibility changes with different numbers of folds. The higher the binder content in Preparation Example 3 (industry standards recognize that a higher binder ratio in polymer materials results in better flexibility), the better the liquid absorption capacity and tensile strength at break after the same number of folds. The S value is also higher than that of Preparation Example 1 after the same number of folds. The thicker foil in Preparation Example 4 (industry standards recognize that a thicker positive electrode current collector results in better flexibility) significantly improves Rs and tensile strength at break after the same number of folds. The S value is also higher than that of Preparation Example 1 after the same number of folds (it can withstand 4 folds). Preparation Example 5 has a higher areal density (industry standards recognize that higher areal density results in poorer flexibility). Its liquid absorption capacity, Rs, and tensile strength all decrease after the same number of folds. The S value is also lower than that of Preparation Example 1 after the same number of folds. Preparation Example 6 has greater compaction compared to Preparation Example 5 (other preparation data for these two groups of electrodes are the same). The data table shows that with increasing folds, its liquid absorption capacity, Rs value, and tensile strength are all worse than those of Preparation Example 5. The S value is also lower than that of Preparation Example 5 after the same number of folds.
[0070] The degradation trends of the three types of indicators are fundamentally different: the liquid absorption volume is the most sensitive to the decline, often decreasing by 30%-50% after the 2nd-3rd bend, responding to the propagation of microcracks and interface peeling; the inverse of the ohmic resistance degradation shows a gradual deterioration, reflecting the cumulative contact damage of the electronic pathway; and the tensile strength drops sharply just before fracture, which is the final signal of the collapse of mechanical load-bearing capacity.
[0071] Weighted model S=α·△W n / △W 基准 +β·R S基准 / R Sn +γ·M n / M 基准 Multidimensional degradation coupling quantification was effectively achieved: when focusing on fast charging performance (β=0.4), such as in preparation examples 2 and 6, the S value decreased more significantly during early bending, confirming the dominant role of ohmic internal resistance in fast charging sensitivity; while when focusing on cycle performance (α=0.4), the liquid retention rate became the key criterion, highlighting the importance of capillary wetting stability for maintaining the long-term electrode structure.
[0072] In summary, this testing method can not only quantitatively distinguish the flexibility characteristics of different process schemes, but also reversely diagnose the dominant failure mode through the evolution trajectory of S-value, providing interpretable and traceable physical property basis for process decisions such as rolling pressure, adhesive formulation, and foil selection.
[0073] Comparative Example This comparative example uses the manual visual folding light transmission judgment method, which is widely used in the current lithium-ion battery manufacturing field, as a reference for the test method of this invention. The specific operation is as follows: Take the positive electrode sheets obtained from Preparation Examples 1 to 6 and let them stand and equilibrate for 2 hours in a constant temperature and humidity laboratory (25±2℃, RH45±5%); manually fold a single electrode sheet once along the center line of its long side (bending angle of 180°), apply uniform finger pressure to fully form the crease, and then slowly flatten it to its original flat state; immediately place the electrode sheet on a standard optical testing platform: the background is an LED diffuse white light source (color temperature 5500K, illuminance 300lx), the observer is 30cm away from the sample, and observe with the naked eye vertically whether the crease area is transparent. The results are statistically summarized in Table 2.
[0074] Table 2
[0075] As can be seen from Table 2, the results have too much overlap, making it impossible to make an effective judgment; at the same time, it is not easy to give a horizontal comparative value to the electrodes with different folding times.
[0076] Finally, it should be noted that the above-described embodiments are merely specific implementations of the present invention, used to illustrate the technical solutions of the present invention, and not to limit it. The scope of protection of the present invention is not limited thereto. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that any person skilled in the art can still modify or easily conceive of changes to the technical solutions described in the foregoing embodiments within the technical scope disclosed in the present invention, or make equivalent substitutions for some of the technical features; and these modifications, changes, or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for testing the flexibility of electrode sheets, characterized in that, Includes the following steps: A. Obtain the initial liquid absorption volume ΔW of the electrode to be tested. 基准 Initial electrode internal resistance R S基准 and initial fracture tensile force M 基准 ; B. After bending the electrode to be tested n times and restoring it to its original shape, test the liquid absorption ΔW of the electrode after n bends. n , electrode internal resistance R Sn and tensile strength at break M n ; Where n is a positive integer and the electrode under test does not break after the nth bending; C. Calculate the electrode flexibility value S after n bends by the changes in liquid absorption, electrode internal resistance and breaking tensile force after n bends. D. The test ends when the electrode breaks.
2. The test method according to claim 1, characterized in that, The method for testing liquid absorption is as follows: Place the electrode to be tested in the electrolyte, so that any position between the crease and the tail end is flush with the liquid surface. After soaking, take it out, drain the surface droplets, weigh it and calculate the mass increment to obtain the liquid absorption. Preferably, the soaking time is 3-6 hours; Preferably, the midpoint line between the crease and the bottom surface of the electrode is aligned with the liquid surface.
3. The test method according to claim 1, characterized in that, The method for testing the ohmic internal resistance of the electrode is as follows: two electrodes to be tested are made into a symmetrical cell and electrochemical impedance spectroscopy (EIS) is used for testing. The scanning frequency is 10 mHz~100 kHz and the amplitude is 10mV. The Rs value corresponding to the real axis intercept in the high-frequency region is extracted as the ohmic internal resistance of the electrode. Preferably, the electrolyte in the symmetrical battery is the same as the electrolyte in the liquid absorption test.
4. The test method according to claim 1, characterized in that, The method for testing tensile strength is as follows: fix both ends of the electrode to be tested in the fixture of the tensile testing machine, stretch it at a constant rate, and record the maximum tensile force value corresponding to the moment the electrode breaks as the tensile strength. Preferably, the stretching rate is 20~100 mm / min.
5. The test method according to any one of claims 1 to 4, characterized in that, The electrode flexibility value S after n bends is positively correlated with the weighted sum of the liquid absorption retention rate of the bent electrode relative to the unbent state, the reciprocal of the degradation of ohmic internal resistance, and the tensile strength retention rate at break.
6. The test method according to claim 5, characterized in that, The liquid absorption retention rate is ΔW n / △W 基准 The inverse of the degradation of the ohmic internal resistance is R. S基准 / R Sn The tensile strength retention rate at break is M. n / M 基准 ; The electrode flexibility value S = α·△W n / △W 基准 +β·R S基准 / R Sn +γ·M n / M 基准 ; Among them, α, β, and γ are weight coefficients respectively, and 0<α<1, 0<β<1, 0<γ<1, α+β+γ=1.
7. The test method according to claim 6, characterized in that, α is the weighting coefficient for cycle performance; β is the weighting coefficient for fast charging performance; γ is the weighting coefficient for winding process adaptability. The values of α, β, and γ are determined by the priority of the corresponding performance requirements in actual engineering.
8. The test method according to claim 7, characterized in that, In practical engineering, when the focus is on the cycle performance of the battery, α ≥ 0.4; Alternatively, in practical engineering, when the focus is on the fast charging performance of the battery, β≥0.4; Alternatively, in practical engineering, when the focus is on the adaptability of the battery winding process, γ≥0.
4.
9. The test method according to any one of claims 1 to 4, characterized in that, The bending is performed along the centerline of the long side of the electrode to be tested; Preferably, the bending angle is 0° to 180° and does not include 0°, and is preferably 90° or 180°.
10. The application of the test method according to any one of claims 1 to 9 in electrode screening, roll forming process optimization, coating / die cutting parameter verification, or electrode quality consistency control.